Depression and Suicidal Ideation in a Sample of Malaysian Healthcare Workers: A Preliminary Study During the COVID-19 Pandemic - Sahimi, Hajar Mohd Salleh; Mohd Daud, Tuti Iryani; Chan, Lai Fong; Shah, Shamsul Azhar; Rahman, Farynna Hana Ab; Nik Jaafar, Nik Ruzyanei (Frontiers in Psychiatry, 2021)
Objective: The burden of suicidal behavior is anticipated to increase as a sequela of the COVID-19 pandemic. However, there is limited evidence on suicidal behavior among healthcare workers, an at-risk population. Our study aimed to investigate suicidal ideation in terms of the rate and associated factors in a sample of Malaysian healthcare workers during the early-phase of the COVID-19 pandemic. Methods: A subpopulation analysis (N=171) was conducted within a larger, nation-wide cross-sectional study of Malaysian healthcare worker psychological distress from March 18-21, 2020. Current suicidal ideation was measured with item 9 of the Patient Health Questionnaire-9 (PHQ-9). The following independent variables were assessed: socio-demographic profile, occupation & service-related factors, health-anxiety (Health Anxiety Inventory, HAI), lifetime anxiety disorder and severity of depression (PHQ-9). Results: The proportion of healthcare workers with current suicidal ideation (19/171) and clinical depression (17/171) were 11.1% and 9.9% respectively. Multivariable analysis showed that clinical depression was the most significant factor associated with current suicidal ideation (p<0.001, OR=55.983, 95%CI=9.015-347.671) followed by mild (subthreshold) depression (p=0.001, OR=15.984 95%CI=2.977-85.804). Service duration of more than 10 years was associated with significantly less suicidal ideation (p=0.049, OR=0.072, 95%CI= 0.005-0.993). Conclusions: Depression (subthreshold & especially within the clinical range) and early-career status (< 10 years in service) may be target areas of early intervention for reduction of suicidal ideation amongst healthcare workers who have served during the COVID-19 pandemic. Further research is warranted to elucidate specific occupational stressors related to COVID-19 work conditions to tailor appropriate suicide preventive strategies in this population.